Pengaruh Kinerja Lingkungan, Profitabilitas, Likuiditas Dan Kepemilikian Institusional Terhadap Pengungkapan Tanggung Jawab Sosial Perusahaan (Studi Empiris pada Perusahaan Sub Sektor Pertambangan Batubara yang Terdaftar di Bursa Efek Indonesia Periode 20 - Hamzah, Amir (IAIN Surakarta, 2019)
This study aims to determine the influence of environmental performance variables, profitability (ROA), liquidity (CR) and institutional ownership, both partially and simultaneously on the disclosure of corporate social responsibility. The samples of this study were 11 coal mining companies. The sampling technique used was purposive sampling. The analysis technique used was panel data regression, hypothesis testing using t-statistics, and f-statistics. The classical assumption test shows that the available data qualifies to use the panel data regression equation model. The results of the test variables of environmental performance, profitability, and liquidity have a significant influence on the disclosure of corporate social responsibility,and Â Institutional ownership has no effect and is significant for disclosure of corporate social responsibility Keywords: Environmental Performance, Profitability, Liquidity, Institutional ownership, Corporate Social Responsibility Disclosure JEL Classification: Q56, C12, G23, G32, G38, O16